Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10549-011-1428-z
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen metabolites as active inhibitors of aromatase in the treatment of breast cancer

Abstract: The mechanism of tamoxifen action in the treatment of breast cancer is believed to be via active metabolites that act as potent estrogen receptor antagonists. Attempts to identify relationships between active metabolite concentrations and clinical outcomes have produced mixed results. Since anti-estrogenic effects may be brought about not only by estrogen antagonism, but also by reduced estrogen synthesis, we tested the ability of tamoxifen and its principal metabolites to inhibit aromatase in vitro. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…The antiestrogenic activity of the most widely used SERM tamoxifen has been thought to be mediated exclusively by antagonism of estrogen binding to the estrogen receptors [3,4]. However, recent studies have shown that important metabolites of tamoxifen, N-desmethyl-tamoxifen and endoxifen, can also act as AIs in vitro [5]. These data are consistent with the observed similarity in side effects of tamoxifen and AIs, including musculoskeletal aches [6] and hot flashes [7,8] seen with both [9,10].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The antiestrogenic activity of the most widely used SERM tamoxifen has been thought to be mediated exclusively by antagonism of estrogen binding to the estrogen receptors [3,4]. However, recent studies have shown that important metabolites of tamoxifen, N-desmethyl-tamoxifen and endoxifen, can also act as AIs in vitro [5]. These data are consistent with the observed similarity in side effects of tamoxifen and AIs, including musculoskeletal aches [6] and hot flashes [7,8] seen with both [9,10].…”
Section: Introductionmentioning
confidence: 59%
“…In previous studies, we have shown that tamoxifen metabolites, including endoxifen and N-desmethyl-tamoxifen, can act as AIs in vitro with K i values of 4 and 15.9 lM, respectively [5]. The present studies demonstrate that norendoxifen is a potent and selective inhibitor of human aromatase with a K i value in the nanomolar range, close to the potency of the positive control used: letrozole (IC 50 of 5.3 nM) [5], which is the most potent AI that is available for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Among tamoxifen metabolites, 4HT and endoxifen have been shown to be SERMs, serving as antagonists of estrogen binding to the ERs (Lim et al, 2005). N-DMT and endoxifen act as AIs with IC 50 values of 6.1 and 20.7 mM, respectively, via noncompetitive mechanisms (Lu et al, 2012a). In previous studies, we have characterized the inhibitory ability of norendoxifen against recombinant CYP19, CYP2B6, CYP2D6, human liver CYP2C9, and CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…It has a complex metabolic profile involving both active and inactive metabolites (Jin et al, 2005). Previous studies have shown that two tamoxifen metabolites, N-desmethyltamoxifen (N-DMT) and 4-hydroxy-N-desmethyltamoxifen (endoxifen), can act as AIs in vitro (Lu et al, 2012a). Recently, N, N-didesmethyl-4-hydroxy-tamoxifen (norendoxifen), another active metabolite of tamoxifen, has also been shown to be a potent AI.…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen is a trans isomer of clomiphene citrate, which is a combination of two isomers that exert both anti-estrogenic and estrogenic effects simultaneously and human studies have confirmed its estrogenic activity to be minimal or negligible (Lin et al, 2010;Lu et al, 2012). Tamoxifen citrate enhances spermatogenesis by increasing FSH, leydig cells sensibility to LH, and testosterone levels, which lacks an intrinsic oestrogenic effect, so it may be more appropriate to use in male infertility (Buvat et al, 1983;Kadioglu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%